2022
DOI: 10.3390/vaccines10030444
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Vaccination and the Bridge between First and Fourth Dose: Where Are We?

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has induced the explosion of vaccine research. Currently, according to the data of the World Health Organization, there are several vaccines in clinical (145) and preclinical (195) stages, while at least 10 are already in clinical phase 4 (post-marketing). Vaccines have proven to be safe, effective, and able to reduce the spread of SARS-CoV-2 infection and its variants, as well as the clinical consequences of the development of coronavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
9
0
2
Order By: Relevance
“…To answer the question of whether the humoral response after the third dose was similar to that after the second dose, the anti-spike-RBD antibody titer 1 month after the second dose (T3) was compared with that 1 month after the third dose (T8 and T9 for Groups 1 and 2, respectively). We found that the booster dose increased the anti-spike-RBD antibody titer 3-fold, which was in agreement with others (22)(23)(24). The changes in nAb titer over time was also assessed, as these antibodies are associated with immune protection against COVID-19 infection (10,25).…”
Section: Discussionsupporting
confidence: 90%
“…To answer the question of whether the humoral response after the third dose was similar to that after the second dose, the anti-spike-RBD antibody titer 1 month after the second dose (T3) was compared with that 1 month after the third dose (T8 and T9 for Groups 1 and 2, respectively). We found that the booster dose increased the anti-spike-RBD antibody titer 3-fold, which was in agreement with others (22)(23)(24). The changes in nAb titer over time was also assessed, as these antibodies are associated with immune protection against COVID-19 infection (10,25).…”
Section: Discussionsupporting
confidence: 90%
“…The negative effect exerted by MMF, ABA, CCS, MTX, JAKi, RTX, and TNFi is partially in line with previously reported information (2,7,21,(36)(37)(38) and it is of relevance independent from the definition of seroconversion. Although a clear cut-off of antibody titer associated with protection is lacking, the data available demonstrates that the protection drops during subsequent months (39) and this supports the policy of administering a third and fourth booster dose (40)(41)(42) and maybe more in the future. Immunosuppressive therapy may lead to a faster loss of protection in IRD patients.…”
Section: Discussionmentioning
confidence: 70%
“…Existing studies support the evidence for booster dose efficacy against both Delta and Omicron variants ( 29 , 30 ). Therefore, many countries have decided to push forward the booster vaccination to as many individuals as possible to achieve maximum public health benefits against the emerging SARS-CoV-2 variants ( 31 ). Identifying factors that influence booster vaccination acceptance will help to determine groups that will most readily accept a booster dose.…”
Section: Discussionmentioning
confidence: 99%